Birth rate, infant mortality, abortion in recent years in various nations - Spaziante, Ermenegildo (Medicina e Morale, 2005)
Nel quadro delle attuali problematiche concernenti la considerazione e la tutela della vita umana sin dal suo insorgere, l'Autore ha esaminato e comparato tre specifici aspetti statistici concernenti i fondamentali parametri della natalità, della mortalità infantile (nel primo anno di vita), la abortività indotta legalmente registrata, per una duplice coorte di Nazioni, l'una costitutita da venti Nazioni di livello socio-economico più elevato, l'altra relativa a venti Nazioni con sviluppo meno elevato, limitando il secondo gruppo ai primi due parametri, stante la diffusa difficoltà di collezionare dati attendibili per quanto concerne la abortività. Per le Nazioni del primo gruppo l'indagine ha prescelto quegli Stati che abitualmente pubblicano i dati statistici degli aborti legali. La comparazione fra i due termini di tempo, a distanza generalmente di quindici anni, consente un quadro abbastaza significativo delle rispettive incidense. La natalità è in via di progressivo e diffuso contenimento, sia pure con varia intensità. La mortalità infantile evidenzia la grande diversità delle situazioni e delle prospettive per la riduzione delle perdite di giovani vite, in rapporto anche con gli aspetti sociali, organizzativi e scientifici della sanità. L'abortività legalmente autorizzata e registrata nelle Nazioni più sviluppate presenta una grande diversità di incidenza statistica, anche nel tempo, e, piiù di recente, probabilmente in rapporto con le più recenti modalità di attuazione, che inducono alla interruzione della vita nascente anche fuori dell'ambiente ospedaliero ed in tempi sempre più precoci, con un crescente rilievo biologico, ma non meno importante per le implicazioni etiche. ---------- The review of the statistical data, comparing the two extremities of the time span considered (for the MDC 1984 and 2000, for the LDC 1982 and 2000), has brought into evidence some significant indications: a) The birth rate is generally in widespread decrease in the first group. The drop is more noted in Russia, Poland, Bulgaria as well as Japan, Canada and Romania. In three nations however is an inversion of this tendency, in varying degrees in Denmark, Norway, Netherlands. In the l.d.c., the drop birth rate is high in some (Iran, Algeria, Morocco, Zimbabwe, Ghana, Bolivia). In others it is less marked (Mali, Uganda, Ethiopia). b) Infant mortality in the MDC is always more restained, the level emphasizes both the greater healht and social commitment and the scientific progress. In the LDC there is a great difference between those countries that have archieved a laudable progress in the control of this parameter (such as Bolivia, Senegal, Iran, Libya), even though not at the level of the MDC, and those countries where there is a high level of infant mortality, immediately after birth and in the first year of life, that is still very distant from usual, more normal levels of acceptabilityâ€¦ and therefore with a high sociological significance that should provoke help from the luckier nationsâ€¦ c) With regard to provoked abortion that is legal and recorded, the statistics emphasize a disparity in the situation and the progression. In the nations of the former Soviet block that had highest levels of abortion, generally there is a drop in the rate although the parameter remains high. In the nations that were not under Marxist rule, generally the abortion rate remains more restained, with a few exceptions; despite this there are elements that lead to the new methods of pregnancy interruption outside of hospital structures and a more widespread use of contraception methods. From the group of indications that can be draw from the statistical data examined, it would seem desirable that there be an increase in conscience and there is a necessity of the promotion of a better culture and a more widespread diffusion of the ethics that surround the defence of the new life coming into being. This should become a fundamental objective of civilization, for a greater accettaption and the right for better protection of human beings at the beginning of life, and more high consideration for the suffering that accompanies not only infant mortality, but also abortion, in the preliminary decision of the woman (not always made freely!) and in the act of abortion itself, with the psychological, pathological and physical trauma that it incurs, that may remain in the memory of the woman as a shocking experience. It is therefore a problem essentially of humanity and civilization, that should be undertaken by the community in a framework that aims to extenuate the serious multiple factors of human existence and pain.